Perspective of Human Condensins Involved in Colorectal Cancer - Wang, Hongzhen; Chen, Yao; Yang, Dawei; Ma, Liang (Frontiers in Pharmacology, 2021)
Although many important roles are played by human condesins in condensation and segregation of mitotic chromosomes, what roles of human condensins play in colorectal cancer are still unclear at present. Recently, abnormal expressions of all eight subunits of human condensins have been found in colorectal cancer and they are expected to become potential biomarkers and therapeutic targets for colorectal cancer in the future. However, there are still no reviews on the significance of abnormal expression of human condensin subunits and colorectal cancer until now. Based on a brief introduction to the discovery and composition of human condensins, the review summarized all abnormally expressed human subunits found in colorectal cancer based on publicly published papers. Moreover, Perspective of application on abnormally expressed human subunits in colorectal cancer is further reviewed.